Queuing Analysis in a Multiuser Diversity System With Adaptive Modulation and Coding Scheme - Kim, Taejoon; Lim, Jong-Tae (IEEE transactions on vehicular technology, 2011)
In wireless packet networks, the performance of multiuser diversity schedulers has been analyzed with the saturation assumption; however, the finite queue length effect should be taken into account. We propose a new scheduling scheme exploiting multiuser diversity that considers not only channel information but queue information as well. Considering the finite queue length effect and adaptive modulation and coding scheme (AMCS), we analyze the performance of the proposed scheduler.